2010
DOI: 10.1111/j.1365-2524.2010.00964.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of domestic abuse for older women: a review of the literature

Abstract: What is known about this topicThe services that currently exist may not be appropriate to meet the needs of this group of women. AbstractThe consequences of domestic abuse are far reaching, impacting significantly on long-term health and emotional wellbeing of those affected. However, while the literature offers an insight into the scope and nature of domestic abuse among the younger population in the UK, there is currently little available data regarding older women and domestic violence. This is increasingly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
61
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 26 publications
(45 reference statements)
4
61
0
3
Order By: Relevance
“…While in the UK it has been estimated that approximately 30% of women and 17% of men between the ages sixteen and fifty-nine years have experienced domestic abuse (Smith et al 2012). Domestic abuse takes many different forms and has been traditionally defined as including physical, psychological, sexual, financial and emotional abuse (Olive, 2007 Those who experience domestic abuse report significant immediate and longer-term health impacts which affect both physical and mental health status (Lacey et al 2013, McGarry et al 2011. However, despite recognition of the consequences that domestic abuse exerts on the health and wellbeing of those affected it is only relatively recently there has been a shift at a policy and service delivery level from the construction of domestic abuse as a largely social problem to its 'reconstruction' and growing recognition as both a health and a social care issue (Lavis et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…While in the UK it has been estimated that approximately 30% of women and 17% of men between the ages sixteen and fifty-nine years have experienced domestic abuse (Smith et al 2012). Domestic abuse takes many different forms and has been traditionally defined as including physical, psychological, sexual, financial and emotional abuse (Olive, 2007 Those who experience domestic abuse report significant immediate and longer-term health impacts which affect both physical and mental health status (Lacey et al 2013, McGarry et al 2011. However, despite recognition of the consequences that domestic abuse exerts on the health and wellbeing of those affected it is only relatively recently there has been a shift at a policy and service delivery level from the construction of domestic abuse as a largely social problem to its 'reconstruction' and growing recognition as both a health and a social care issue (Lavis et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The impact of DVA on the lives and health of those affected is now well documented within the literature and this includes increased mortality and morbidity, both physical and psychological ill-health, effecting both short and longer term health and wellbeing (Rose et al, 2011, McGarry, et al, 2011. DVA also exerts a detrimental impact on the health and wellbeing of wider family members, especially children (Holt et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This assumption is mainly based on a limited number of studies investigating the prevalence of physical or sexual intimate partner violence among older women and the general criminological theory that 4 Journal of Interpersonal Violence intimate partner violence among older women are also both physical and psychological (Fisher, Zink, & Regan, 2011;Mouton, 2003). They include trauma-related injuries and physical conditions, such as gastrointestinal disorders, genito-urinary, and musculo-skeletal disorders (McGarry, Simpson, & Hinchliff Smith, 2011). For example, Mouton's (2003) study of 1,245 community dwelling women aged 50 to 79 years found increased rates of poorer mental health among older women who experienced intimate partner violence.…”
Section: Introductionmentioning
confidence: 99%
“…While there is consensus that older women who report intimate partner violence also have poorer physical and psychological health, it remains unclear if the violence affects them more or less. On one hand, it is assumed that the impact that intimate partner violence has on women's health decreases with women's increased age, as levels of physical and sexual violence decrease and women might have devised strategies to deal with the negative impact of violence over time (McGarry et al, 2011). On the other hand, it is argued that the health of women experiencing intimate partner violence might be worse for older women as they may need to deal with the cumulative effects of long-term intimate partner violence (Penhale & Porritt, 2010), and because they are more used to internalizing the problem (Fisher et al, 2011;Romito, Turan, & De Marchi, 2005).…”
Section: Introductionmentioning
confidence: 99%